Study of loneliness and wisdom in 482 middle-aged and oldest-old adults: a comparison between people in Cilento, Italy and San Diego, USA. (2nd November 2021) - Jeste, Dilip V.; Di Somma, Salvatore; Lee, Ellen E.; Nguyen, Tanya T.; Scalcione, Mara; Biaggi, Alice; Daly, Rebecca; Liu, Jinyuan; Tu, Xin; Ziedonis, Douglas; Glorioso, Danielle; Antonini, Paola; et al.
Abstract: Objectives: There has been growing research interest in loneliness and wisdom in recent decades, but no cross-cultural comparisons of these constructs using standardized rating measures in older adults, especially the oldest-old. This was a cross-sectional study of loneliness and wisdom comparing middle-aged and oldest-old adults in Cilento, Italy and San Diego, United States. Method: We examined loneliness and wisdom, using the UCLA Loneliness Scale Version 3 (UCLA-3) and San Diego Wisdom Scale (SD-WISE), respectively, in four subject groups: adults aged 50-65 and those ≥90 years from Cilento, Italy ( N = 212 and 47, respectively) and San Diego, California, USA ( N = 138 and 85, respectively). Results: After controlling for education, there were no significant group differences in levels of loneliness, while on SD-WISE the Cilento ≥90 group had lower scores compared to the other three groups. There was a strong inverse correlation between loneliness and wisdom in each of the four subject groups. Loneliness was negatively associated while wisdom was positively associated with general health, sleep quality, and happiness in most groups, with varying levels of significance. Conclusion: These results largely support cross-cultural validity of the constructs of loneliness and wisdom, and extend previous findings of strong inverse correlations between these two entities. Loneliness has become a growing public health problem, and the results of our study suggest that wisdom could be a protective factor against loneliness, although alternative explanations are also possible. Research on interventions to reduce loneliness by enhancing wisdom in older adults is needed.